Cement applicator use for hip resurfacing arthroplasty. Issue 5 (May 2015) - Jaeger, Sebastian; Rieger, Johannes S.; Obermeyer, Beate; Klotz, Matthias C.; Kretzer, J. Philippe; Bitsch, Rudi G.
Highlights An experimental study of different cementing techniques. Comparison of a new cement applicator with the recommended technique for the BHR. The applicator appears to be effective for a homogenous cement distribution. The new cement applicator technique showed no cement defects or air trapping. The cement applicator technique showed a lower risk of over-penetration.